Relações filogenéticas em Geophagini (Acanthopterygii, Cichlidae), utilizando caracteres miológicos. - Deprá, Gabriel de Carvalho (2019)
Although several studies have dealt with the description of morphological characters in Cichlidae, usually aiming for phylogenetic inference, little attention has been given to their musculature. The complete striated musculature of a cichlid species, Geophagus sveni Lucinda, Lucena & Assis, was described for the first time, with illustrations of all muscles and a protocol for the dissection of specimens. The striated musculature of at least of species of each genus in tribe Geophagini, among other cichlids, was compared, and 98 characters were described with the purpose of analysing their relation with the group’s phylogeny. This character matrix was employed to produce two unconstrained phylogenetic analyses, one weighted and the other unweighted. The myological characters were mapped upon a pre-existing phylogenetic hypothesis, for understanding the correlation among the characters and trophic specialisations of each taxon. The conclusion is that Geophagini specialised in sifting substrate (winnowers) tend to present a few convergent adaptations, manifested in the shape and degree of development of muscles such as adductor mandibulae, levator arcus palatini, dilatator operculi, adductor branchialis 1 and obliqui ventrales 1–2. This study facilitates future investigations on the functions of the striated muscles in fishes and their role in the processes of adaptive radiation, i.e., functional diversification.